A genetic approach to identify amino acids in Gcn1 required for Gcn2 activation (poster) - Schiemann A; Gottfried S; Sattlegger E (Massey University)
The General Amino Acid Control stress signalling pathway allows cells to sense and overcome starvation. One of the major players in this pathway is the protein kinase Gcn2 found in all eukaryotic cells. Activation of Gcn2 leads to phosphorylation of the alpha subunit of eukaryotic translation initiation factor (eIF2α), which then leads to the re-programming of the cell’s gene transcription and translation profile, and ultimately allowing cells to cope with and overcome starvation. For sensing starvation, Gcn2 must directly bind to its effector protein Gcn1. This interaction is mediated via a region in Gcn1 called the RWD binding domain (RWDBD). Overexpression of the RWDBD alone impairs Gcn2 activation through disrupting endogenous Gcn1-Gcn2 interaction, hampering eIF2α phosphorylation, and consequently cells cannot overcome starvation and fail to grow.  This dominant negative phenotype is dependent on Arg-2259 in RWDBD.  Taking advantage of this phenotype in yeast, we here found that the dominant negative phenotype was reverted by each of four amino acid substitutions, K2270A, R2289A, R2297A, and K2301A.  This correlated with increased eIF2α phosphorylation levels, suggesting their relevance for Gcn2 activation.  All but Lys-2270 are fully surface exposed, suggesting that these amino acids may directly contact Gcn2.  We also found amino acid substitutions that enhanced the dominant negative phenotype of the overexpressed RWDBD, and correlated with further reduction in eIF2α-P levels.  Our findings suggest that two helices in Gcn1 constitute at least one Gcn2 contact point.